PENGARUH LAMA PENYIMPANAN ENTRES DALAM MEDIA SIMPAN TERHADAP TINGKAT KEBERHASILAN OKULASI TANAMAN KARET (Hevea brasiliensis Muell. Arg.) KLON PB 260 - Rostian Nafery; Eddy Usman; Miranty Trinawaty; Suradi SP (Universitas Tridinanti Palembang, 2016)
Effect of Long Storage entres in Media Store Against Rubber Plant GraftingSuccess Rate (Hevea brasiliensis Muell. Arg) clone PB 260. This study aims to assess theOld Influence Storage entres In Store Media Success Rate Against Plant Grafting Rubber(Hevea brasiliensis) clone PB 260. This research has been conducted in the VillageDistrict of Sembawa Sembawa Banyuasin, with a height of 10 m above sea level. Thisstudy was conducted from September 2014 to November 2014. This study used aRandomized Block Design (RBD), at 4 (four) experimental media store, with longstorage consists of 8 (eight) level and repeated three (3) times. Each experimental unitconsisted of 5 (five) buds and require 480 trial plants. Parameters observation that thepercentage of successful grafting after 30 days (%), shoots mentis (stalk/day), shootheight (cm), number of leaves (strands). The results showed Media store sawdust (M1)show that is capable of storing entres for 1 day resulted in grafting success rate after 30days by 80%, bud stalk mentis 0.19 stalk/day, shoots as high as 18.16 cm high, and thenumber leaves as much as 41 strands. Media store coco (M2) shows that is capable ofstoring entres for 1 day resulted in a success rate of grafting after 30 days at 100%, budstalk mentis 0.29 stalk/day, shoots as high as 13.3 cm high, and the number of leaves of30 strands. Media store banana (M3) indicates that is capable of storing entres for 1 dayresulted in a success rate of grafting after 30 days at 100%, bud stalk mentis 0.37stalk/day, shoots as high as 18.33 cm high, and the number of leaves as much as 49strands. Media store newsprint (M4) show that is capable of storing entres for 1 dayresulted in grafting success rate after 30 days by 70%, bud stalk mentis 0.14 stalk/day,shoots as high as 10.2 cm height and number of leaves as much as 42 strands.Keyword : Long storage, Media store, Entres PB260